Pengetahuan Remaja dan Akses Informasi terhadap Sikap dalam Praktik Kesehatan Reproduksi Remaja - Endang Susilowati; Nilatul Izah; Fitriana Rakhimah (Jurnal Profesi Bidan Indonesia, 2023)
Background: Population data shows that teenagers are the largest group. Reproductive health is very important for teenagers to implement, because in the current era many teenagers are ignorant about their reproductive health. The importance of knowledge and parental monitoring is one of the factors for adolescents in implementing adolescent reproductive health practices. Objective: This research aims to determine the influence of adolescent knowledge and the role of parents in providing information about reproductive health on adolescent attitudes towards reproductive health. Method: This research is a quantitative research with a cross-sectional approach. The population in this study were students of the Muhammadiyah I Vocational School class in Tegal City. The sampling technique will be carried out using simple random sampling. The number of samples in this study was 30 respondents. Data analysis was carried out using univariate and bivariate analysis, univariate analysis was carried out by making a frequency table for each variable. Bivariate analysis was carried out using the Kendall's tau test with α = 0.05. Results: The research results show that the majority of respondents implement good reproductive health practices, namely 23 respondents (76.7%), the level of knowledge influences reproductive health practices with an analysis result of 0.041 and access to information shows a value of 0.046. Conclusion: There is an influence between knowledge and access to information and reproductive health practices